Identification and Distribution of Plants that have the Potential as Natural Dyes for Ikat Weaving in Malacca District (Agrikan Jurnal Agribisnis Perikanan, 2022)
Malacca Regency is one of the regencies in East Nusa Tenggara Province as a producer of â€œtenun ikatâ€ fabrics which have a distinctive style using natural dyes. The increased exploitation and use of ZPA sourced from plants will cause a reduction in natural dyes and pose a threat to their availability. The increasing need for the use of plants as natural dyes causes a reduction in natural dyes and poses a threat to their availability. This study aims to determine the identification and distribution of natural dye plants that are used by woven craftsmen in Malacca Regency is needed as a conservation effort to ensure the availability of dye plants. The dye plants found and used by woven woven craftsmen in Malacca Regency (Builaran Village, Lakulo, Babotin Maemina Village and Litamali Village) totaling 18 identified species consisting of 11 families namely Rubiceae, Fabaceae, Aracaceae, Lamiaceae, Phyllanthus, Rhizoporaceae, Myrtaceae, Meliaceae, Symplocaceae, Zingiberacea. On the distribution map, the dye plant species Symplocos SP from the Symplocaceae family was not found. Natural coloring plants can also grow varied on each slope.
Keywords: Identifikasi; SebaranZat Pewarna Alami; Tenun Ikat